(untitled) (Research, Society and Development, 2021)
Introduction: Patient Safety in a Neonatal Intensive Care Unit is to reduce as little as possible the risk of causing harmful acts in the course of care. Objective: This study aimed to search together with the scientific literature which factors compromise patient safety in the neonatal care unit. Methods: For this an integrative review was performed on the Pubmed and Scielo platforms, using a combination of the descriptors “Patient Safety” or “Patient Safety” and “Neonatology” or “Neonatology” and “Hospital” and “Infection” or “Infection”. 27 articles that after the inclusion and exclusion criteria were analyzed and totaled in 7 manuscripts for the study. Results: The results showed that patient safety is compromised by factors related to multiprofessional work and the treatment received. Conclusion: Proposals include the elaboration of tools (protocols, checklists, among others) that could effectively help the establishment of a safety culture and promote the theme.